2021
DOI: 10.1002/cmdc.202100139
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and in vivo Distribution of Intracellular Delivered Macrolide Short‐Chain Fatty Acid Derivatives

Abstract: Short-chain fatty acids (SCFAs) have a range of effects in metabolism and immune regulation. We have observed that delivery of SCFAs to lysosomes has potent immune regulatory effects, possibly as a surrogate signal for the presence of anaerobic organisms. To better understand the pharmacology of lysosomal SCFA donors, we investigated the distribution and metabolism of propionate and butyrate donors. Each analog (1 a and 2 a) can donate three SCFA equivalents via ester hydrolysis through six intermediate metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 68 publications
5
13
0
Order By: Relevance
“…uptake of Azithromycin into immune cells [25] which we confirmed in a previous study demonstrating beneficial distribution patterns (spleen, liver and lung) for anti-inflammatory effect after oral application [28]. Although some previous studies showed a possible effect of Azithromycin in psoriasis, our focus was on understanding the efficacy of fumarates.…”
supporting
confidence: 76%
See 1 more Smart Citation
“…uptake of Azithromycin into immune cells [25] which we confirmed in a previous study demonstrating beneficial distribution patterns (spleen, liver and lung) for anti-inflammatory effect after oral application [28]. Although some previous studies showed a possible effect of Azithromycin in psoriasis, our focus was on understanding the efficacy of fumarates.…”
supporting
confidence: 76%
“…and organs collected 2 and 4 h after treatment. Collected samples stored at -25 °C until further processing, as published [28].…”
Section: Pharmacokinetic Studiesmentioning
confidence: 99%
“…CSY5669 and its metabolites were quantified using liquid chromatography coupled to a triple quadrupole MSMS detector (API 4500, Sciex, Canada) as described previously ( 45 ). Briefly, samples were homogenized in 6 volumes of acetonitrile, and the resulting supernatant was separated via reverse phase chromatography followed by mass-specific detection.…”
Section: Methodsmentioning
confidence: 99%
“…Frozen organ samples were thawed and treated as described earlier [20]. Briefly, samples were digested with Proteinase K in a buffer volume in µL corresponding to sample weight in mg (Proteinase K, VWR, diluted 1:40 in phosphate buffer 20 mM) for 1 h at 50 °C and homogenized at 6 m/s for 40 s (FastPrep-24 5G, MP Biomedicals).…”
Section: Sample Preparation For Pharmacokinetic Assessmentmentioning
confidence: 99%